Asymmetric Cell Division of Fibroblasts is An Early Deterministic Step to Generate Elite Cells during Cell Reprogramming. Issue 7 (25th February 2021) - Song, Yang; Soto, Jennifer; Wang, Pingping; An, Qin; Zhang, Xuexiang; Hong, SoonGweon; Lee, Luke P.; Fan, Guoping; Yang, Li; Li, Song
Abstract: Cell reprogramming is considered a stochastic process, and it is not clear which cells are prone to be reprogrammed and whether a deterministic step exists. Here, asymmetric cell division (ACD) at the early stage of induced neuronal (iN) reprogramming is shown to play a deterministic role in generating elite cells for reprogramming. Within one day, fibroblasts underwent ACD, with one daughter cell being converted into an iN precursor and the other one remaining as a fibroblast. Inhibition of ACD significantly inhibited iN conversion. Moreover, the daughter cells showed asymmetric DNA segregation and histone marks during cytokinesis, and the cells inheriting newly replicated DNA strands during ACD became iN precursors. These results unravel a deterministic step at the early phase of cell reprogramming and demonstrate a novel role of ACD in cell phenotype change. This work also supports a novel hypothesis that daughter cells with newly replicated DNA strands are elite cells for reprogramming, which remains to be tested in various reprogramming processes. Abstract : The asymmetric cell division (ACD) of fibroblasts at the early stage of reprogramming plays a key role in cell fate determination and enables the generation of "elite cells" during cell reprogramming. An "asymmetric reprogramming hypothesis" is proposed, whereby cells with newly replicated DNA strands after ACD may have more epigenetic plasticity for reprogramming.